2020
DOI: 10.1002/suco.201900248
|View full text |Cite
|
Sign up to set email alerts
|

Experimental shear tests of reinforced concrete beams with corroded longitudinal reinforcement

Abstract: In this study, shear tests were conducted to investigate the effect of corrosion damage induced in longitudinal reinforcement on the shear resistance mechanisms of reinforced concrete (RC) members without transverse reinforcement. A total of eight RC beam specimens were carefully designed and fabricated, and accelerated corrosion and typical shear tests were conducted considering various anchorage conditions and corrosion rates that were introduced in the longitudinal tension reinforcement as the key test vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
3
6
0
Order By: Relevance
“…With the sufficient anchorage performance, the bond deterioration caused by corrosion cracks in the shear span may lead to tied-arch action with the increasing of shear capacity. Furthermore, it shares the same agreement with the research work conducted by Han et al [13], in which the tension reinforcement was properly anchored using the hook details, the RC beams subjected to less than 5% corrosion degree showed about 40% enhancement in shear resistance capacity due to the transfer mechanism shifting from beam action to tied-arch action, regardless of the reduction in bond performance.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…With the sufficient anchorage performance, the bond deterioration caused by corrosion cracks in the shear span may lead to tied-arch action with the increasing of shear capacity. Furthermore, it shares the same agreement with the research work conducted by Han et al [13], in which the tension reinforcement was properly anchored using the hook details, the RC beams subjected to less than 5% corrosion degree showed about 40% enhancement in shear resistance capacity due to the transfer mechanism shifting from beam action to tied-arch action, regardless of the reduction in bond performance.…”
Section: Introductionsupporting
confidence: 89%
“…However, in the case of the beams C3-1 and C3-2 having the target corrosion degree of 3.16% and 3.10%, respectively, the shear strength was increased by approximately 7% (37.5 kN versus 35 kN on average) while in the case of the beams C4-1 and C4-2 the maximum capacity is nearly equal to the result of the control beams in group C0. These results can be explained that the bond stress between steel and concrete increases in the experimental beams having the corrosion degree smaller than 4% regardless of the corrosion crack occurred along the longitudinal rebars that is mentioned in the literature [13,15]. The higher corrosion degree beams C5-1 and C5-2 displayed lower initial stiffness than the other tested beams with no clear shear crack was found in the beam web but the flexural cracks during testing.…”
Section: Experimental Shear Capacitysupporting
confidence: 54%
“…In this study, FE analysis was conducted on the shear test of RC beams with corroded tensile reinforcement (Han et al 2020) to verify the rationality of the numerical model introduced in Section 2. Han et al (2020) fabricated eight RC beams using the corrosion degree ( corr ω ) and anchorage detail of tensile reinforcement as key variables. As shown in Fig.…”
Section: Collected Shear Test and Its Modeling Processmentioning
confidence: 99%
“…Meanwhile, Azam (2010), Xue and Seki (2010), and Han et al (2020) experimentally observed that depending on the anchorage details of tensile reinforcement, the shear strength of corroded RC members may increase compared with that of non-corroded RC members. As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation